Comparison of Phenolics and Phenolic Acid Profiles in Conjunction with Oxygen Radical Absorbing Capacity (ORAC) in Berries of Vaccinium arctostaphylos L. and V. myrtillus L. - Colak Nesrin; Torun Hülya; Gruz Jiri; Strnad Miroslav; Subrtova Michaela; Inceer Huseyin; Ayaz Faik Ahmet (Polish Journal of Food and Nutrition Sciences)
Caucasian blueberry (Vaccinium arctostaphylos L.) and bilberry (V. myrtillus L.), both native to Turkey, were evaluated for their total phenolics (TP) and anthocyanin (TAC) contents. Individual compositions of free phenolic acids and phenolic acids liberated from ester and glycoside forms were analyzed using UPLC-MS/MS. Berry extracts of each species were separated into three different fractions (sugar/acid, polyphenolic and anthocyanin) by solid phase extraction (SPE). The anthocyanin fractions of each species had the highest level of TP and TAC contents and ORAC values. Each species contained 10 phenolic acids representing each fraction, but in different quantities. The phenolic acids liberated from the esters and glycoside forms were caffeic acid and p-coumaric acid. The fractions containing phenolic acids liberated from ester and glycoside forms had a higher antioxidant capacity than that from free phenolic acids. The data suggest that both berries have potential as good dietary sources of phenolic antioxidants.